Strengthening district management as a key lever in health system strengthening: bottom up innovation in two district health systems in South Africa - Orgill, Marsha (Department of Public Health and Family Medicine, 2025)
It is widely recognised that the District Health System (DHS) is an effective vehicle for institutionalising Primary Health Care (PHC) - and establishing an effective DHS to improve access to health services has been an explicit South African government goal since 2003. Whilst there has been progress towards this goal, there have also been challenges. These include a persistent management skills' deficit at district level, in the context of an already under resourced health system. To address this challenge, the competencies of managers and the capabilities of management teams must be strengthened. Against this background, this PhD sought to understand how, why and in which contexts the capacity development of managers can be nurtured within the South African DHS, applying a bottom-up perspective considering district-level experience. More specifically, I sought to understand the processes, tactics and strategies within the DHS that trigger mechanisms to effect change in management capacity and support system strengthening. A South African national policy process offered the opportunity for this research. In 2012 - 2017, the National Department of Health piloted reforms toward National Health Insurance (NHI) in eleven health district pilot sites across the country, focusing on strengthening and re-engineering PHC. As part of this reform, the Minister of Health called for district management and leadership to be strengthened. The overarching methodology of the PhD was realist evaluation, and a case study design was used. An initial context mapping process allowed understanding the broader context of reform and supported the development of programme theories in each of two case study sites. The programme theories were then tested and refined through empirical research in each site. Through the cross-case analysis, I then refined my Middle Range Theory - the final product of a realist evaluation. Key findings include that senior DHS managers drew on their tacit knowledge, understanding of local context, formal training, and systems thinking and sensemaking skills to design innovations to develop the competencies and capabilities of managers and the capacity of structures in the district health system. From a bottom-up perspective, capacity development in health districts was an emergent process, that was led by district managers. It combined the natural diffusion of ideas and intentional efforts to delegate and disseminate a range of tasks and activities toward nurturing systemic capacity in the district. They worked only with existing resources. The managers used their positional authority and sensegiving skills (using carrots, sticks and sermons), to motivate staff and to develop individual, team and structural capacity. At the same time, prioritising management strengthening as part of nationally-led reforms stimulated systemic capacity development at the district level. Key lessons are that: management capacity development should be integrated within routine health system functioning; formal training should be complemented by workplace-based learning; training should enable managers to lead systemic capacity development, team development and broader system strengthening; and large-scale processes of health system strengthening must prioritise system capacity development within the DHS. Overall, this PhD contributes to the evidence base on how to nurture management and systemic capacity development within the district health system in less well-resourced contexts.